2007
DOI: 10.1152/ajplung.00095.2006
|View full text |Cite
|
Sign up to set email alerts
|

Increased lung expansion alters lung growth but not alveolar epithelial cell differentiation in newborn lambs

Abstract: Although increased lung expansion markedly alters lung growth and epithelial cell differentiation during fetal life, the effect of increasing lung expansion after birth is unknown. We hypothesized that increased basal lung expansion, caused by ventilating newborn lambs with a positive end-expiratory pressure (PEEP), would stimulate lung growth and alter alveolar epithelial cell (AEC) proportions and decrease surfactant protein mRNA levels. Two groups of lambs were sedated and ventilated with either 0 cmH(2)O P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Congenital diaphragmatic hernia prevents in utero lung expansion and results in hypoplastic lungs, 25,26 and complete congenital airway obstruction prevents lung fluid from leaving the trachea and produces a large, hyperplastic lung. 27 Animal models of in utero congenital diaphragmatic hernia have shown that fetal trachea occlusion increases the lungs' distending pressure and results in increased fetal lung growth, 28,29 capillary growth, and epithelial branching. [30][31][32][33] The mechanical strain from CPAP applied to the lungs of young animals can stimulate lung growth and have other beneficial molecular effects.…”
Section: Discussionmentioning
confidence: 99%
“…Congenital diaphragmatic hernia prevents in utero lung expansion and results in hypoplastic lungs, 25,26 and complete congenital airway obstruction prevents lung fluid from leaving the trachea and produces a large, hyperplastic lung. 27 Animal models of in utero congenital diaphragmatic hernia have shown that fetal trachea occlusion increases the lungs' distending pressure and results in increased fetal lung growth, 28,29 capillary growth, and epithelial branching. [30][31][32][33] The mechanical strain from CPAP applied to the lungs of young animals can stimulate lung growth and have other beneficial molecular effects.…”
Section: Discussionmentioning
confidence: 99%
“…De Zabala and Weinmann [27] had indicated earlier that the alveolar maturation lasted beyond the fetal period and might extend up into the early postuterine period. Evidence for this assumption could be found in the experimental studies on fetal sheep and lambs by Flecknoe et al [16, 55]. These authors showed that in the last trimester of gestation of sheep fetuses, the sum of the alveolar endothelial cells (AEC) of type II increases disproportionately.…”
Section: Discussionmentioning
confidence: 98%
“…This is illustrated by the studies of continuous static expansion in sheep. When done in the fetus, the proportion of AEC1 cells went up markedly (27), but this was not seen with high versus low PEEP ventilation in 2-week-old lambs (38). …”
Section: Damage To Aec1 Cellsmentioning
confidence: 98%